2013
DOI: 10.1063/1.4774246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and scaling laws of nanoporous gold

Abstract: Nanoporous metals are a class of novel nanomaterials with potential applications in many fields such as sensing, catalysis, and fuel cells. The present paper is aimed to investigate atomic mechanisms associated with the uniaxial tensile deformation behavior of nanoporous gold. A phase field method is adopted to generate the bicontinuous open-cell porous microstructure of the material. Molecular dynamics simulations then reveal that the uniaxial tensile deformation in such porous materials is accompanied by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 45 publications
10
99
0
Order By: Relevance
“…Several numerical simulation studies have used that process to create microstructures that closely resemble experimental NPG. [25,36,48] It is therefore remarkable that spinodal structures with unequal phase fractions are known to disintegrate during coarsening. [49,50] For NPG this implies that networks with low ϕ may exhibit a reduced connectivity density of their load-bearing paths, which would make them anomalously weak and compliant.…”
Section: Role Of Network Connectivity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several numerical simulation studies have used that process to create microstructures that closely resemble experimental NPG. [25,36,48] It is therefore remarkable that spinodal structures with unequal phase fractions are known to disintegrate during coarsening. [49,50] For NPG this implies that networks with low ϕ may exhibit a reduced connectivity density of their load-bearing paths, which would make them anomalously weak and compliant.…”
Section: Role Of Network Connectivity?mentioning
confidence: 99%
“…Several of these studies even either report or even presuppose agreement, [2,5,7,12,13,16] while others discuss corrections. [22,23,36,37] Thus, even though it is now widely realized that the Gibson-Ashby scaling relations are not designed for network structures such as NPG, these relations remain indispensable as a starting point for discussing scaling in that material.…”
Section: Scaling Lawsmentioning
confidence: 99%
“…where C2 and C3 are proportionality constants [6]. Along a different line, Liu and Antoniou demonstrated that mass agglomeration at ligament junctions can remarkably affect elastic behavior, inducing a stiffening of the NP metal foam [7].…”
Section: Phenomenological Modeling Of Mechanical Propertiesmentioning
confidence: 99%
“…In this case, the model exhibited clear limitations, which gave rise to various attempts of modifying the functional dependence of model equations on experimental variables without changing fundamental assumptions [3][4][5][6]. However, recent experimental and theoretical work has definitely shown that limitations arise exactly in connection with the fundamental assumptions of Gibson and Ashby's model, namely the negligible aggregation of mass at ligament junctions and the identification of ligaments with thin beams [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation